Perencanaan Perkerasan Kaku (Rigid Pavement) - Nurul Ilham; Syafridal Is (Jurnal Teknik Sipil Unaya, 2019)
This plan aims to plan rigid pavement with a planned age of 20 years with a predicted traffic growth of 4% and the planned concrete quality is K350. In the Rigid Pavement (Rigid Pavement) Planning using concrete paving connected with reinforcement. The planned steel tensile stress is 230 MPa. Reinforcement for the elongated direction used 2 pieces of reinforcement with a diameter of D12-100 mm and for the transverse direction used 2 transverse reinforcement with a diameter of D12-250 mm. Dowels used for rigid pavement planning are 25 mm in diameter, 450 mm long, and 300 mm apart. In this plan used reinforcement with the same diameter for each segment, namely D12-100 mm for longitudinal reinforcement and D12-250 mm for transverse reinforcement.Keywords: Degree of Saturation, Road Performance, MKJI 1997, Traffic Volume.